Case report and review of literature: IgG4-gastroduodenitis in upper GI Crohn’s disease: two separate entities or just a marker of disease severity? - Desmedt, Valérie; Geldof, Jeroen; Hoorens, Anne; Lobaton, Triana (Frontiers in Medicine, 2024)
A 20-year old male presented with ulcerative gastritis and duodenitis complicated by pyloric stenosis. Helicobacter pylori infection was excluded and the lesions did not respond to treatment with proton pump inhibitors. No other parts of the intestinal tract showed signs of inflammation.Histopathological review showed signs of chronic inflammation with granuloma formation. A tentative diagnosis of isolated upper gastrointestinal (GI) Crohn's disease was made. However, additional work-up revealed significantly positive IgG4-staining as well as elevated IgG4 serum levels. Since granulomatous disease is unlikely in IgG4-related disease, an eventual diagnosis of overlapping IgG4-related disease and Crohn's disease (CD) was made. Treatment with systemic steroids and anti-TNF in combination with azathioprine led to rapid symptomatic improvement.In this manuscript, we review the available literature on IgG4-related gastroduodenitis, granulomatous gastritis and upper GI Crohn's disease. We suggest the possibility that IgG4infiltration may be a marker of severely active inflammatory bowel disease, rather than a separate disease entity.